ENERGISING RASA THEORY: BREATH, EMPATHY, AND WELL-BEING IN CONTEMPORARY ACTOR TRAINING - Mallika Prasad; Ram Ganesh Kamatham (Arts Academy)
Breath has emerged as the preferred locus of performance energy over the last two decades, presenting a pragmatic approach to questions of contemporary actor training, postStanislavskian approaches (such as psychophysical approaches) and vitalisation of traditional performance practices (such as Kutiyattam and Kalaripayattu). In this paper, we elaborate outwards from this “rediscovery” of breath, to offer a methodological base from which to engage the concept of Rasa which occupies a pre-eminent position within Indian aesthetics. We argue that the constellation of bodily practices arising from within this field of knowledge, far from esoteric traditionalisms, inform the neuro-physiological basis for empathy. Practical engagement with these neuro-physiological processes widens understanding of the importance and role of well-being in contemporary actor training. We argue that a shift towards this well-being based approach within conservatories and performance training institutes, is a necessary adaptation to meet the challenges of a postpandemic world.